UDK 338.12 FOURTH INDUSTRIAL REVOLUTION IN THE TEXTILE AND GARMENT MANUFACTURING - Khudayberdiev, Otabek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article is devoted to an overview of the current state, problems and prospects for the development of domestic textile and garment manufacturing, means and methods of process automation using the fourth industrial revolution (Industry 4.0). The necessity of introducing new technologies, computerization and automation of production, the use of machine learning technologies and artificial intelligence is substantiated.